QUALITY OF LIFE IN POLISH FARMERS’ HOUSEHOLDS ASSESSMENT WITH TOPSIS METHOD - Głowicka-Wołoszyn, Romana; Wołoszyn, Andrzej; Wysocki, Feliks (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
The aim of the research was a multidimensional assessment of the quality of life in farmers’ households along with its synthetic measure and a typology of household classes, rendered by the measure. The 2015 data on 730 farmers’ households were used to analyse their quality of life in nine dimensions: material living conditions, employment, health, education, leisure and social relations, economic and physical security, civic participation, environmental quality, and the subjective assessment of well-being. Due to concomitance of features measured on metric and non-metric scales, generalized distance measure (GDM) was applied as part of the TOPSIS method to determine the distance of objects from the model values. The study drew on microdata from the Social Diagnosis survey conducted in 2015 by the Council for Social Monitoring, and employed clusterSim R-package for calculations.